Peran Lingkungan Kerja dalam Meningkatkan Kinerja Karyawan: Sebuah Tinjauan Bibliometrik - Abdurrafi, Muhammad Rizky (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
This study aims to examine the role of the work environment in improving employee performance through a bibliometric analysis of scientific literature published between 1991 and 2024. The relationship between workplace conditions and employee productivity is explored using a systematic approach based on data extracted from the Scopus database. The research methodology applies a comprehensive bibliometric analysis utilizing VOSviewer software to map and analyze 105 scientific documents. The literature search focused on the keywords